Diseño e implementación de un CRM (Customer Relationship Management) para optimizar la relación con el cliente en la Asociación Batallón de Honor de Ingenieros “General José María Córdova”, año 2014. - Andrade Guzmán, Adriana Raquel (2014)
The objetive of this research is to develop and implement a Customer Relationship Management (CRM) in the Association of Honor Battalion of Engineers "General José María Córdova" in the city of Quito, with the aim to optimize the client relationship -company; and, in this way achieve excellence in the service provided by the association, improving the benefits they receive. To determine the importance that provides the implementation of a CRM a theoretical framework and the necessary justifications where developed. Population, operationalization of variables and surveys were developed for the partners and authorities. The results determined that the Association does not have a CRM application that allow to manage effectively the data of its partners; and, therefore, the relationship with them is not appropriate, causing frustration and even the loss of customers. The research sets up an alternative solution to the problem presented and proposes to develop and deploy a CRM to generate a repository of information that would strengthen the relationship between the partners and the Battalion of Honor Engineers "General José María Córdova" by fostering business development supported in the application of new technologies.